Customized Technological Designs to Improve the Traditional Use of Rosa canina Fruits in Foods and Ingredients - Adina Andreea Teodorescu; Ștefania Adelina Milea; Bogdan Păcularu-Burada; Oana Viorela Nistor; Doina Georgeta Andronoiu; Gabriela Râpeanu; Nicoleta Stănciuc (Plants, 2023)
The rosehip fruits from Romanian spontaneous flora were valorized in three different customized variants, including jellified products, juices, and a nutraceutical. Prior to the technological design, the rosehip samples were characterized for individual polyphenolic content. The samples (non)-enzymatically treated showed epicatechin as the major compound, whereas the enzymatic treatment enhanced the extraction of quercetin (40.23 ± 0.48 mg/100 g DW extract), gallic acid (9.74 ± 0.24 mg/100 g DW extract), and kaempferol. Different ratios and types of sugars were added to obtain jellified products, leading to a significantly different bioactive profile. The sugar-free and steviol samples showed the highest content in carotenoids (89.36 ± 0.06 mg/g dry weight (DW) and 39.22 ± 1.16 mg/g DW, respectively), leading to the highest antioxidant activity (8.19 ± 0.80 mMol Trolox/g DW and 20.16 ± 0.31 mMol Trolox/g DW, respectively). The gelling capacity increased with the increase in sugar content. The enzymatically treated rosehip fruit pulp was mixed in various ratios with apple juice, followed by pasteurization. The polyphenolic content was approximately two times higher in the blended juices (20.75 ± 1.40 mg gallic acid equivalents (GAE)/100 mL). The overall impression highlighted the preferences of panelists for sugar-free products, whereas adding apple juice significantly influenced their preferences. The fresh pulp was enhanced with pectin, followed by inoculation with Lactobacillus acidophilus, and freeze-dried showed satisfactory cell viability (approximately 7 log CFU/g DW), whereas an antidiabetic, anti-tyrosinase and anti-obesity potential of the powder was suggested. Our results provide enough evidence for customized processing of rosehip fruits in foods and nutraceuticals as a response to consumers’ choices, highlighting the bioactive compounds and nutrient contents, whereas selected in vitro health-related evidence was suggested.